MANFAAT PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) MENURUT SISWA KELAS IV MADRASAH IBTIDAIYAH MA’HAD AL- ZAYTUN INDRAMAYU 2024 - Wilda Alfiana; Henri Peranginangin; Dewi Utami (STKIP Subang, 2024)
This study aims to explore the opinions of Grade IV students of Madrasah Ibtidaiyah Ma'had Al-Zaytun Indramayu about the benefits of clean and healthy living behaviors (PHBS) to be used as evaluation material, especially learning about personal health and the environment. This is important in the context of students' lives in the present and future. This study uses a qualitative description approach; Data collection was carried out by interview, observation, and documentation techniques. To check the validity of the data, source tringulation is used, namely the integration of data from various sources. The results of the study show that the benefits of Clean and Healthy Living Behavior (PHBS) according to Grade IV Students of Madrasah Ibtidaiyah Ma'had Al-Zaytun Indramayu 2024 are: (a) reducing the risk of developing diseases; (b) prevent them from infection and disease; (c) improvement of students' physical health; (d) supporting physical conditions to stay healthy; (e) support a more effective learning process; (f) form positive habits that they will carry into adulthood; especially the habit of maintaining personal and environmental cleanliness; and (g) increasing social awareness, namely by reminding friends to implement PHBS. Teachers' efforts to improve understanding and behavior of clean and healthy living for grade IV students of madrasah ibtidaiyah Ma'had Al-Zaytun through a holistic educational approach and practical activities made by teachers, namely grade IV students can understand and apply clean and healthy living behaviors well. Keywords: Benefits, Behavior, Clean and Healthy Living Behavior, Ma'had Al-Zaytun;